The Development of Multicultural Islamic Education in the Modern Era: Relevance and Challenges - Khasanah, Uswatun (Letiges, 2023)
Multicultural Islamic Education is an education that emphasizes multiculturalism as one of the visions of education with the main character that is inclusive, egalitarian, and humanist but remains firmly based on spiritual and divine values based on the Qur'an and Sunnah. The type of research used is the qualitative method with a phenomenological approach. This research collected data through in-depth interviews, observation, and documentation. Researchers conducted epoché, followed by data analysis with three stages, namely data collection, data reduction, data presentation, and conclusion drawing/verification. The study's results demonstrate the relevance of developing multicultural Islamic education in the modern era, which provides high respect and guarantees for each individual. Therefore, it is incorrect to assume that Islamic education lacks humanistic elements. Furthermore, the study's findings indicate that the development of multicultural Islamic education is not a simple task. This study found challenges and obstacles in formulating and adopting multiculturalism in the world of Islamic education, including: differences in the boundaries of multiculturalism as an ideology, exclusivism in homogeneous groups, vague tolerance boundaries that have the potential to cause egocentrism, the selection of appropriate multicultural models and types for Islamic education, and the feasibility and readiness of each component of the Islamic education system. The study's results suggest several ways to enhance multicultural Islamic education, including the need to keep refining the discourse of multicultural Islamic education. Second, that must continue to deepen and explore the concept of education, which upholds values, beliefs, heterogeneity, plurality, diversity, and all aspects of community life within the context of studying Islamic teachings based on the Qur'an and Sunnah. Third, further research is needed to establish the concept and form of multicultural Islamic education that can be implemented in practice.